“Drowning Brain in a Pool of CSF” — A Rare Complication of Periencephalic Subdural Panhygroma following Removal of a Posterior Fossa Tumor - Behera, Bikash Ranjan; Deo, Ram Chandra; Mishra, Sanjib; Biswal, Jyotirmayee; Das, Deepak (Indian Journal of Neurosurgery, 2018)
Posterior fossa tumors are commonly encountered in pediatric age group patients. Most of these tumors present with features of hydrocephalus in the child. Conventionally, these cases are managed by suboccipital craniotomy with decompression of the tumor mass to establish the free flow of cerebrospinal fluid (CSF) across fourth ventricle and aqueduct of Sylvius. Following resection of posterior fossa tumor, appearance of subdural hygroma is a rare phenomenon.Though few cases of subdural hygroma are reported in literature following foramen magnum decompression in Chiari's malformation, their appearance following posterior fossa tumor resection is alien to medical literature and limited to only two case reports. Here the authors present a patient with periencephalic subdural panhygroma (PSP) following posterior fossa tumor resection who was successfully treated with a ventriculoperitoneal shunt (VPS) to accomplish a symptomatic and radiologic remission.
Keywords: posterior fossa tumor resection; periencephalic subdural panhygroma; ventriculoperitoneal shunt